Dampak Lingkungan Keluarga terhadap Prestasi Belajar Siswa Sekolah Dasar di Era Digital SDN Keraton 2 (Eduscotech, 2024)
This study examines the influence of family environment on the academic achievement of elementary school students in the digital era. Using a quantitative correlational approach, data were collected through questionnaires, observations, and documentation involving fourth-grade students at SDN Keraton 2. The findings indicate a significant positive relationship between parental attention, learning motivation, and students’ mathematics performance. Parents who provide emotional support, guidance, and structured study routines contribute to higher academic outcomes. Conversely, lack of supervision and excessive gadget use tend to reduce motivation and focus. The study highlights the crucial role of family engagement in optimizing children’s learning and adapting educational practices to digital challenges. These results provide theoretical and practical implications for teachers and parents in basic education.